2014
DOI: 10.3390/en7117094
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Heat Transfer and Pressure Drop Characteristics of H-type Finned Tube Banks

Abstract: H-type finned tube heat exchanger elements maintain a high capacity for heat transfer, possess superior self-cleaning properties and retain the ability to effect flue gas waste heat recovery in boiler renovations. In this paper, the heat transfer and pressure drop characteristics of H-type finned tube banks are studied via an experimental open high-temperature wind tunnel system. The effects of fin width, fin height, fin pitch and air velocity on fin efficiency, convective heat transfer coefficient, integrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 9 publications
(11 reference statements)
0
24
0
1
Order By: Relevance
“…It is observed that heat transfer coefficients are higher for wavy fins than flat fin not only due to the increase in surface area but also because air follows a longer channel passage and helps in better mixing of air. However, the pressure drop is not too much when wavy fins are used; researchers have also used the louvered fin, the H type wavy fin, the flat fin and studied their performances . However, the wavy fin and the tube configuration still attract many researchers due to their reliability.…”
Section: Introductionmentioning
confidence: 99%
“…It is observed that heat transfer coefficients are higher for wavy fins than flat fin not only due to the increase in surface area but also because air follows a longer channel passage and helps in better mixing of air. However, the pressure drop is not too much when wavy fins are used; researchers have also used the louvered fin, the H type wavy fin, the flat fin and studied their performances . However, the wavy fin and the tube configuration still attract many researchers due to their reliability.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [18] conducted an experiment to measure heat transfer and pressure drops inside H-type finned tube banks. Based on their experimental results, they suggested correlations among the fin efficiency, Nusselt number, and Euler number.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to results of studies [2,3], thermo-aerodynamic and mass-dimensional characteristics of the "petal-type" finning only in certain cases can compete with spiral-tape finning.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%